On the shape of the magnetic Barkhausen noise profile for better revelation of the effect of microstructures on the magnetisation process in ferritic steels - Vashista M.; Moorthy V. (My University, 2025)
Abstract The shape of the Magnetic Barkhausen Noise (MBN) profiles has been compared for two different methods of MBN measurements in order to reveal the true extent of the influence of different carbon-content related microstructures on the magnetisation process. The MBN profiles were measured using high frequency and low frequency MBN measurement systems on samples from low carbon 18CrNiMo5 steel and high carbon 42CrMo4 steel heat treated by isothermal annealing, spheroidising annealing and quenching and tempering processes. The high frequency MBN (HFMBN) profile shows only a single peak for all the samples due to insufficient applied magnetic field strength and shallow skin-depth of detection of HFMBN signals. The low frequency MBN (LFMBN) profile shows two peaks for all the samples due to larger magnetisation range revealing the difference in the interaction of domain walls with different microstructural features such as ferrite, pearlite, martensite and carbides. The shape of the LFMBN profile shows systematic and distinct variation in the magnetisation process with respect to carbon content and different microstructures. This study shows that the LFMBN profile reveals distinct changes in shape which could be successfully used for characterisation of different microstructural phases in ferritic steels. © 2015 Elsevier B.V.